2022
DOI: 10.17582/journal.pjz/20201108111148
|View full text |Cite
|
Sign up to set email alerts
|

Diet Composition and Feeding Strategy of Butis koilomatodon Inhabiting the Estuarine Regions in the Mekong Delta, Vietnam

Abstract: Authors' Contribution QMD, TTHL and YTNN conceived and developed the study. QMD, YTNN and TMN conducted fieldwork and contributed to data collection. QMD, TTHL and TTKN performed the analysis. QMD and TTHL wrote the manuscript. QMD, TTHL, YTNN and TTKN contributed to editing the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This demonstrated that the efficiency of DNA barcoding in species identification was high. In the same way, several previous studies showed that the body sizes of B. humeralis in TDST were larger than in HBBL [ 9 ] and also that DDCM was the sampling site where TL and W values of B. butis were lower than HBBL [ 10 ]. However, in clusters III and IV, they were grouped.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This demonstrated that the efficiency of DNA barcoding in species identification was high. In the same way, several previous studies showed that the body sizes of B. humeralis in TDST were larger than in HBBL [ 9 ] and also that DDCM was the sampling site where TL and W values of B. butis were lower than HBBL [ 10 ]. However, in clusters III and IV, they were grouped.…”
Section: Discussionmentioning
confidence: 69%
“…Morphometric and meristic parameters, including fish weight (W), total length (TL), body depth (BD), head length (HL), eye diameter (ED), the distance between eyes (DE), ED/HL, DE/HL, BD/TL, HL/TL in previous studies [ [8] , [9] , [10] ], were re-analyzed in the present study. The Shapiro-Wilk test examined the normal distribution of these parameters [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…chrysospilos spawns all year round, highly concentrated in the wet season (July to October). According to Dinh et al (2022a), the fecundity of the batch ranges from 2,614 to 23,465 eggs/female and is proportional to the fish's total length and body weight. Ps.…”
Section: Introductionmentioning
confidence: 99%
“…"During the breeding season, females have swollen abdomen while in males, the genital papilla (which is present only in males) becomes very prominent. The success of good scientific planning and management of fish species largely depends on the knowledge of their biological aspects, in which food and feeding habits include a precious portion" [6,7]. The study of food and feeding habits of fish have manifold importance in fishery biology and fisheries management, it was playing crucial role in day to day fish conservation practices has been proven earlier scientific works [8,9].…”
Section: Introductionmentioning
confidence: 99%